The outpost [videorecording (DVD)] - Lurie, Rod, 1962-; Eastwood, Scott, 1986-; Jones, Caleb Landry; Bloom, Orlando, 1977-; Tapper, Jake (Screen Media Films, 2020)
In Afghanistan, a small unit of American soldiers fight against an overwhelming force of Taliban insurgents.